EUTHANASIA BETWEEN THE RIGHT TO LIVE AND THE FREEDOM TO DIE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Promoting and respecting the fundamental human rights and freedoms is a barrier against violence, abuse, but also a guarantee of individual and social morality.Following a brief introduction, this article provides some definitions of euthanasia, while aiming to bring to the reader’s attention the way in which the concept has emerged and developed throughout history. Subsequently, we shall present some criteria for the classification of euthanasia, but some pros and cons also, which tension the ethical, medical, legal, and religious debates about the legalization of euthanasia. Towards the end, we shall visit a few dilemmas gravitating on the subject, and also present some biblical principles, which should be the perspective from which the issue of euthanasia is to be considered. The worst thing, when we talk about euthanasia, is that the whole system of values, which was seen as a good one from the very beginning, is now overthrown. The battle for life, the supreme value that gave birth to Hippocrates’ medicine, is substituted for the battle for death.